Patient and Graft Survival After A1/A2-incompatible Living Donor Kidney Transplantation - Shivani S. Bisen, BA; Samantha N. Getsin, BA; Po-Yu Chiang, MD, MPH; Kayleigh Herrick-Reynolds, MD; Laura B. Zeiser, ScM; Sile Yu, MD; Niraj M. Desai, MD; Fawaz Al Ammary, MD, PhD; Kyle R. Jackson, MD, PhD; Dorry L. Segev, MD, PhD; Allan B. Massie, PhD, MHS (Transplantation Direct, 2022)
Background. ABO type B and O kidney transplant candidates have increased difficulty identifying a compatible donor for living donor kidney transplantation (LDKT) and are harder to match in kidney paired donation registries. A2-incompatible (A2i) LDKT increases access to LDKT for these patients. To better inform living donor selection, we evaluated the association between A2i LDKT and patient and graft survival. Methods. We used weighted Cox regression to compare mortality, death-censored graft failure, and all-cause graft loss in A2i versus ABO-compatible (ABOc) recipients. Results. Using Scientific Registry of Transplant Recipients data 2000–2019, we identified 345 A2i LDKT recipients. Mortality was comparable among A2i and ABOc recipients; weighted 1-/5-/10-y mortality was 0.9%/6.5%/24.2%, respectively, among A2i LDKT recipients versus 1.4%/7.7%/22.2%, respectively, among ABOc LDKT recipients (weighted hazard ratio [wHR], 0.811.041.33; P = 0.8). However, A2i recipients faced higher risk of death-censored graft failure; weighted 1-/5-/10-y graft failure was 5.7%/11.6%/22.4% for A2i versus 1.7%/7.5%/17.2% for ABOc recipients (wHR in year 1 = 2.243.565.66; through year 5 = 1.251.782.53; through year 10 = 1.151.552.07). By comparison, 1-/5-/10-y wHRs for A1-incompatible recipients were 0.631.966.08/0.390.942.27/0.390.831.74. Conclusions. A2i LDKT is generally safe, but A2i donor/recipient pairs should be counseled about the increased risk of graft failure and be monitored as closely as their A1-incompatible counterparts posttransplant.